Further insights into the Stellaria media aggregate (Caryophyllaceae, Alsinoideae, Alsineae) in Africa: first reports of S. ruderalis in North Africa and S. cupaniana in Tunisia, with nomenclatural notes on the name Alsine cupaniana - El Mokni, Ridha; Del Guacchio, Emanuele; Iamonico, Duilio (Phytotaxa, 2023)
Stellaria ruderalis and S. cupaniana (Caryophyllaceae, Alsinoideae, Alsineae) are recorded from Tunisia for the first time, S. ruderalis being also new to continental Africa. Descriptions, notes on habitat, ecology, and distribution in Tunisia are given. Original photographs together with a key to the Stellaria taxa of Tunisia are also provided. The typification of the name Alsine cupaniana is discussed and a specimen preserved at LY is designated as the lectotype.